EXPLORING THE STUDENTS’ READING STRATEGIES ON TENTH GRADE OF SENIOR HIGH SCHOOL - Muhammad Fatkhul Munjid; Tauricha Astiyandha (Fakultas Keguruan dan Ilmu Pendidikan | Universitas Islam As-Syafi'iyah, 2021)
Reading is a must skill for the students no matter the level of proficiency, Reading skill that is used in all subject in the school, using reading they can understand what they learn and obtain information about subject that help develop their skills. In this term reading strategies play an important role in defining the success of reading. Many researchers have found that reading by using strategies are able to help students to read effectively and efficiently, this issue is very interesting because success in reading is supported by the strategies the reader uses when reading. Therefore, the researcher is interested in finding out what reading strategies high school students use. The aim of this study is to examine the reading strategies used by Senior High School students while comprehending descriptive text and their perception about reading strategy. The research design was qualitative approach based on the theory of case study. The informant consist of five students of tenth grade Senior High School. Observation and individual interviews are instruments used by the researcher to collect data, then the data is analyzed by triangulation, which consists of reduction data, display data and conclusion drawing. The results of this study show that there were 7 strategies used by participants namely repeated reading, taking notes, imagine the content, summarizing, bottom up, guessing, getting the purpose of reading, each participant uses more than one strategy in reading, The result also showed that the strategies the students used while reading greatly helped them understand the text and made the reading process more effective and efficient.